2016
DOI: 10.1016/j.geomorph.2015.03.035
|View full text |Cite
|
Sign up to set email alerts
|

Short-term post-wildfire dry-ravel processes in a chaparral fluvial system

Abstract: Dry ravel, the transport of sediment by gravity, transfers material from steep hillslopes to valley bottoms during dry conditions. Following wildfire, dry ravel greatly increases in the absence of vegetation on hillslopes, thereby contributing to sediment supply at the landscape scale. Dry ravel has been documented as a dominant hillslope erosion mechanism following wildfire in chaparral environments in southern California. However, alteration after initial deposition is not well understood, making prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 17 publications
2
19
0
Order By: Relevance
“…The initial dry‐ravel sediment pulse released after the 2013 Springs Fire formed dry‐ravel deposits along channel margins measured in the contiguous lower and upper portion of the study reach and upstream through the burned zone shortly after the fire stored 0.21 m 3 /m of sediment (~107.5 m 3 over a 504 m channel length). Of the total volume within this longer reach, ~70.9 m 3 remained after the 2014 storm, suggesting that 34% was mobilized and transported (comparable to that measured for the lower portion of the reach alone, reported in Florsheim et al , ). This sediment eroded from dry ravel deposits accounted for 34% of the volume of the deposit that filled the lower portion of the reach during the 2014 storm.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…The initial dry‐ravel sediment pulse released after the 2013 Springs Fire formed dry‐ravel deposits along channel margins measured in the contiguous lower and upper portion of the study reach and upstream through the burned zone shortly after the fire stored 0.21 m 3 /m of sediment (~107.5 m 3 over a 504 m channel length). Of the total volume within this longer reach, ~70.9 m 3 remained after the 2014 storm, suggesting that 34% was mobilized and transported (comparable to that measured for the lower portion of the reach alone, reported in Florsheim et al , ). This sediment eroded from dry ravel deposits accounted for 34% of the volume of the deposit that filled the lower portion of the reach during the 2014 storm.…”
Section: Resultssupporting
confidence: 80%
“…The total volume V T of sediment stored in the n dry‐ravel deposits for the reach is: V T = Σ V c i + Σ V r i where i = 1, …, n . In the present study, dry‐ravel volumes reported in Florsheim et al () for the lower portion of the study reach are extended upstream through the burned area.…”
Section: Methodssupporting
confidence: 48%
See 3 more Smart Citations